Toward Harmonised Governance of Cultural Routes: Sicilian Industrial Heritage Conservation Without Valorisation - Costanzo, Carlotta; Noto, Alessio (European Scientific Journal, ESJ, 2025)
Sicily represents an emblematic case of industrial heritage governance in Italy. Despite the absence of specific legislation, the region holds a historically significant legacy, particularly linked to the sulphur mining industry. In the absence of a unified legal and policy framework, valorisation increasingly depends on local communities and grassroots initiatives. The study adopted a case study approach, selecting Sicily for its complex governance system and long-standing engagement with cultural heritage policies. Therefore, it combined a multilevel review of national and regional legislation with semi-structured interviews conducted through the key informant method at the Sicilian sites of Trabia-Tallarita and Floristella-Grottacalda. Documentary and interview data have been cross-referenced, highlighting the relationship between European priorities, national policy frameworks and local practices. Findings reveal a misalignment between European valorisation strategies and regional implementation, underscoring the need for cohesive governance, strengthened local capacity, and sustainable funding. Within such a framework, Sicily requires a coordinated national strategy to align local cultural initiatives with European standards and ensure effective heritage valorisation.